2023
DOI: 10.3389/fphar.2023.1088957
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine alleviates MPTP-induced nigrostriatal damage through modulation of JNK and ERK signaling pathways in the mice model of Parkinson’s disease

Abstract: Introduction: Nicotine (Nic) has previously been proven to reduce neurodegeneration in the models of Parkinson’s disease (PD). The present study is intended to investigate the detailed mechanisms related to the potential neuroprotective effects of Nic in vivo.Methods: We established a PD model using 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced C57BL6 mice (25 mg/kg/d, 5 d, i.p.) to investigate the neuropharmacological modulation of Nic pretreatment (2.5 mg/kg/d, 5 d, i.p., 30 min before MPTP inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 77 publications
1
8
0
Order By: Relevance
“…Our results align with several previous studies demonstrating that Nic can increase DA and its metabolites, DOPAC and HVA, in the brains of MPTP-treated mice (Janson et al, 1992;Gao et al, 1998). A similar increase in TH has been noted following Nic administration in mice with Parkinsonism induced by MPTP (Parain et al, 2003;Ruan et al, 2023). There are two possible ways to minimize MPTP neurotoxicity: 1) by inhibiting the formation of the active neurotoxin MPP + from MPTP (Heikkila et al, 1984) and 2) by blocking the uptake of MPP + into the DA neurons (Javitch et al, 1985;Sundström et al, 1986).…”
Section: Discussionsupporting
confidence: 92%
“…Our results align with several previous studies demonstrating that Nic can increase DA and its metabolites, DOPAC and HVA, in the brains of MPTP-treated mice (Janson et al, 1992;Gao et al, 1998). A similar increase in TH has been noted following Nic administration in mice with Parkinsonism induced by MPTP (Parain et al, 2003;Ruan et al, 2023). There are two possible ways to minimize MPTP neurotoxicity: 1) by inhibiting the formation of the active neurotoxin MPP + from MPTP (Heikkila et al, 1984) and 2) by blocking the uptake of MPP + into the DA neurons (Javitch et al, 1985;Sundström et al, 1986).…”
Section: Discussionsupporting
confidence: 92%
“…[26][27][28] Previous studies have shown that cerebral ischemia is closely related to p38MAPK and JNKs. 8,29 As p38MAPK activation is involved in ischemia-induced neurological injury, blocking it may protect brain tissue from ischemia damage by decreasing the production of inflammatory mediators and blocking the inflammatory process. 8 Additionally, inhibiting JNK activation protects against cell death following ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…The next day the mice were placed on the stationary rotating rod device and the speed was increased from 5 to 40 rpm/min within 300 s. The time from start to drop was recorded and repeated three times for each mouse. The suspension experimental apparatus was constructed by fixing a smooth wire with a diameter of 1.5 mm and a length of 30 cm at a height of 50 cm above the ground on two parallel pieces of cardboard using a glue gun [ 24 ]. The two front mouse paws were placed in the mid-point of the 30 cm horizontal wire.…”
Section: Methodsmentioning
confidence: 99%